The Influence of Principal Leadership and Teacher Professionalism on Honorary Teacher Performance - Hayumita, Yantri; Soesanto, Soesanto (Educational Management, 2021)
The purpose of this study was to analyze the effect of principal leadership on teacher performance, the effect of professionalism on teacher performance, and the effect of principal leadership and teacher professionalism together on teacher performance. The population is all public elementary school teachers in SD Dabin III, Selomerto District, and the sample size is determined by the Krejcie table as many as 60 people. Data collection techniques using a questionnaire. Analysis of research results using descriptive statistics, and regression analysis. The results showed that the leadership of the principal, teacher professionalism, and teacher performance were in a good category. The results showed that there is a positive and significant effect of principal’s leadership on teacher performance, professionalism has a positive and significant effect on teacher performance. The results showed that there is a positive and significant joint influence of principal leadership and teacher professionalism on the performance of elementary school teachers. Based on this research, it is suggested that teacher performance needs to be improved and teachers must be aware that rights and obligations must be balanced. The professionalism has been well maintained and improved again considering it has a dominant influence on teacher performance.